PENGARUH WORK ENGAGEMENT DAN MANAGEMENT SUPPORT TERHADAP JOB SATISFACTION DAN KNOWLEDGE SHARING PADA KARYAWAN BANK BRI KC PONTIANAK - Veronica, Rizka; Hendri, M Irfani; Daud, Ilzar (Equator Journal of Management and Entrepreneurship (EJME), 2024)
Knowledge has become capital that is really needed by companies which can enable companies to continue to develop in the current era of globalization. So Bank BRI Pontianak Branch needs to improve the quality of its human resource skills through the knowledge of each employee regarding banking. To support success in improving employee work performance, efforts that can be made by the management and employees of Bank BRI Pontianak are by sharing knowledge. In the knowledge sharing process, work engagement factors and top management support support knowledge sharing activities. Individuals are objects and subjects who share knowledge, while management is the driving force for creating an environment and culture that can influence job satisfaction thereby encouraging employees to exchange knowledge, experience and skills, between employees through all divisions within the scope of Bank BRI Pontianak.This research aims to analyze the influence of work engagement and management support on job satisfaction and knowledge sharing. This research method is causality, because this research aims to explain the variables through testing hypotheses that have been previously formulated. The sample for this research was all employees of Bank BRI Pontianak, totaling 50 employees. The analysis technique used is path analysis with SPSS. The results of this research show that the work engagement variable has a significant positive effect on job satisfaction, management support has a positive but not significant effect on job satisfaction, work engagement has a significant positive effect on knowledge sharing, management support has a positive but not significant effect on knowledge sharing, and job satisfaction has a positive effect significant to knowledge sharing. Job satisfaction does not mediate the relationship between work engagement and management support on knowledge sharing.    Keyword : Work Engagmement, Management Support, Job Satisfaction, Knowledge Sharing